Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Problem Based Learning di SDN 09 Bandar Buat Kota Padang - Checa Alveoleta; Farida Suardiman (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this study is to describe the improvement of the learning process with the problem based learning model in class IV SDN 09 Bandar Buat, Padang city . This type of research is classroom action research, with qualitative and quantitative approaches. The subjects of this study were students and fourth grade teachers of SDN 09 Bandar Buat  Padang city. The results of the study on observation of RPP cycle I Meeting I 84.4%, in the first cycle meeting II 88.88%, in the second cycle 96.66%. The implementation of the teacher aspects of the first cycle of meeting I 83.3%. The first cycle of the second meeting was 92.85%. In the second cycle of 100% the implementation of aspects of students in the first cycle of meeting I 78.6%, in the first cycle of meeting II 92.85%. And in cycle II 100%. It can be concluded that the problem based learning model can show improving the integrated thematic learning process at SDN 09 Bandar Buat, Padang City.